2020
DOI: 10.1021/acsomega.0c04246
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Functionalization of Cellulose Nanocrystals with 2-Isocyanatoethyl Methacrylate and Formation of Composites with Poly(methyl methacrylate)

Abstract: Cellulose nanocrystals (CNCs) derived from renewable plant-based materials exhibit strong potential for improving properties of polymers by their dispersal in the polymer matrix as a composite phase. However, the hydrophilicity and low thermal stability of CNCs lead to compromised particle dispersibility in common polymers and limit the processing conditions of polymer–CNC composites, respectively. One route that has been explored is the modification of CNCs to alter surface chemistry. Acrylic materials are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…between cellulose nanocrystals and IEM. A small increment of the absorption between 2900 and 3000 cm À1 , and the increased CdH stretch of the methyl group of IEM indicates functionalization [24]. Similar studies that reported the use of IR in confirming functionalization include alginate [25], methoxylated pectin and amidated LMP [13], chitosan functionalization with the PNIPAAm [26], cellulosepropargylated chitosan [27], Melamine-Functionalized Chitosan: [28], etc.…”
Section: Uv-vis Region Spectra Of the Bacterial Cellulose Samples Wit...mentioning
confidence: 57%
See 3 more Smart Citations
“…between cellulose nanocrystals and IEM. A small increment of the absorption between 2900 and 3000 cm À1 , and the increased CdH stretch of the methyl group of IEM indicates functionalization [24]. Similar studies that reported the use of IR in confirming functionalization include alginate [25], methoxylated pectin and amidated LMP [13], chitosan functionalization with the PNIPAAm [26], cellulosepropargylated chitosan [27], Melamine-Functionalized Chitosan: [28], etc.…”
Section: Uv-vis Region Spectra Of the Bacterial Cellulose Samples Wit...mentioning
confidence: 57%
“…It gives some idea about the NBC chemical structure, and morphology, for example, the amount and orientation of crystalline phases in semi-crystalline NBCs and the domain sizes in phase-separated polymeric NBCs [31]. ATR-FTIR spectra of Unmodified Cellulose nanocrystals (umCNC), modified Cellulose nanocrystals (mCNC), and 2-isocyanatoethyl methacrylate (IEM) [24].…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the XRD result, it is obvious that activation of hydroxyl groups on the CNCs surface with CDI and reaction with Cys can destroy the intermolecular and intramolecular hydrogen bonds leading to the change of CNCs’ crystalline region. In the case of Q4-CNC, forming the macromolecular layer on the surface of CNCs by radical polymerization might further change the molecular arrangement of the crystalline part or increase the amorphous content . Additionally, it demonstrates the successful grafting of the Cys linker and Q-PDMAEA onto the CNC.…”
Section: Resultsmentioning
confidence: 98%